BACE1 Dependent Neuregulin Processing: Review - Fleck, Daniel; N. Garratt, Alistair; Haass, Christian; Willem, Michael (Current Alzheimer Research, 2012)
Neuregulin-1 (NRG1), known also as heregulin, acetylcholine receptor inducing activity (ARIA), glial growth factor (GGF), or sensory and motor neuron derived factor (SMDF), plays essential roles in several developmental processes, and is required also later in life. Many variants of NRG1 are produced via alternative splicing and usage of distinct promoters. All contain an epidermal growth factor (EGF)-like domain, which alone is sufficient to bind and activate the cognate receptors, members of the ErbB family. NRG1 mediated signaling is crucial for cardiogenesis and the development of the mammary gland and ErbB2 (HER2), an orphan co-receptor for NRG1 is the target of the drug Herceptin® (trastuzumab) used for treatment of metastatic breast cancer. In the nervous system, NRG1 controls the early development of subpopulations of neural crest cells. In particular, NRG1 acts as an essential paracrine signaling molecule expressed on the axonal surface, where it signals to Schwann cells throughout development and regulates the thickness of the myelin sheath. NRG1 is required also by other cell types in the nervous system, for instance as an axonal signal released by proprioceptive afferents to induce development of the muscle spindle, and it controls aspects of cortical interneuron development as well as the formation of thalamocortical projections. Work from several laboratories implicates dysregulation of NRG1/ErbB4 signaling in the etiology of schizophrenia. Biochemical studies have shown that the precursor proteins of NRG1 can be released from the membrane through limited proteolysis. In addition, most NRG1 isoforms contain a transmembrane domain, which is processed by γ-secretase after shedding. Thereby the intracellular domain is released into the cytoplasm. Despite this, the importance of NRG1 cleavage for its functions in vivo remained unclear until recently. β- Secretase (β-site amyloid precursor protein cleaving enzyme 1, BACE1) was first identified through its function as the rate limiting enzyme of amyloid-β-peptide (Aβ) production. Aβ is the major component of amyloid plaques in Alzheimer's disease (AD). More recently it was shown that Neuregulin-1 is a major physiological substrate of BACE1 during early postnatal development. Mutant mice lacking BACE1 display severe hypomyelination of peripheral nerves similar to that seen in mice lacking NRG1/ErbB signaling in Schwann cells, and a BACE1-dependent activation of NRG1 in the process of peripheral myelination was proposed. Here we summarize the current knowledge about the role of NRG1 proteolysis for ErbB receptor mediated signaling during development and in Alzheimer's disease.
Keywords: CRD-Neuregulin